Proposed nonlinear microring resonator arrangement for stopping and storing light - Yupapin, Preecha P.; Pornsuwancharoen, Nithiroth (My University, 2009)
A simple system of an all-optical system for stopping and storing is proposed. A system consists of two microring and a nanoring resonators that can be integrated into a single system. The large bandwidth is generated by a soliton pulse within a Kerrtype nonlinear medium where an all-optical adiabatic and pulse bandwidth compression can be performed. The balance between the dispersion and nonlinear lengths of the soliton pulse exhibits the soliton behavior known as self-phase modulation, which produces a constant optical output. This means that light pulse can be trapped, i.e., stopped optically within the nanowaveguide. © 2009 IEEE.
Keywords: Optical memory; Stopped light; Stored light